Synthesis and Antimicrobial Study of Some New Chlorosubstituted 4-Aroyl Isoxazolines - V. Parhate, Vandana; Maurya, M.R.; Rajput, P.R.; Wagh, P.P.; Rai, M.K. (Asian Journal of Chemistry, 2010)
Some new chlorosubstituted 4-aroyl isoxalines (2a-d) have been synthesized by the interaction of chlorosubstituted 3-aroyl flavanones (1a-d) with NH2OH·HCl in DMSO containing a few drops of piperidine. The structural assignments of these compounds are based on their elemental analysis, chemical properties and spectral data. The newly synthesized chlorosubstituted 4-aroylisoxazolines were evaluated for their antimicrobial activity against E. coli, S. aureus, P. aeruginosa, P. vulgaris by disc diffusion method. The antibacterial results obtained are very encouraging.